Chitosan elicitor stimulation of in vitro growth and ex vitro acclimatization of Lantana camara L. - Veraplakorn, Varaporn; Kudan, Sanya (Agriculture and Natural Resources, 2021)
The efficiency of chitosan on in vitro growth and ex vitro acclimatization of lantana (Lantana camara L.) was compared to thidiazuron (TDZ) or indole-3-butyric acid (IBA). It was found that chitosan promoted in vitro shoot regeneration. Lantana shoots cultured on Murashige and Skoog (MS) medium supplemented with 2.8 mg/L TDZ and 0.1 mg/L high molecular weight chitosan (HMC) produced the highest shoot number of 14.2 ± 6.1 shoots with long lengths of the main shoot and axillary shoot of 3.95 ± 0.96 cm and 0.29 ± 0.12 cm, respectively. Plantlets cultured on MS medium supplemented with 0.1–0.5 mg/L low molecular weight chitosan (LMC) or HMC had root induction of 73.7–94.7% and axillary shoot proliferation of 50.0–61.6%. After transplanting, the plantlets were treated with foliar and soil applications of 0.6 mg/L HMC of 5 mL three times weekly. The chitosan treatment increased the survival percentage and growth of plantlets ex vitro. Plantlets obtained from the MS medium supplemented with 1.5 mg/L IBA and 0.3 mg/L HMC or with only 0.3 mg/L HMC had high survival rates of 82.0% and 81.0%, respectively. The highest fresh and dry weights were for the plantlets derived from the MS medium supplemented with 1.5 mg/L IBA and 0.3 mg/L HMC. Chitosan treatment after transplanting could increase the survival percentage. In addition, the highest biomass resulted from applying both in vitro and ex vitro treatments. This suggested chitosan could be a stimulator for lantana shoot growth in vitro and for acclimatization ex vitro.